Modelling Facebook features in supporting senior entrepreneurship / Marlina Muhamad - Muhamad, Marlina Muhamad (2023)
The concept of "productive aging" can be achieved through participation in either monetary or non-monetary activities. This study focuses on monetary activities involving the elderlies who retired from former employment and became first-time senior entrepreneurs. In this study, senior entrepreneurs are defined as those who are 60years old under the Minimum Retirement Age Act 2012, including retirees who opted for early retirement at age 50. Senior entrepreneurs are associated with lower technical skills; thus, the use of ICT becomes a challenge for them. However, this difficulty could be mitigated by providing them with simple, familiar, recognizable, and flexible ICT that suits their needs. Past studies have agreed that social media platforms such as Facebook are widely used by entrepreneurs. However, senior entrepreneurs are different from young entrepreneurs because their main motivation to become entrepreneurs after retirement is mostly dominated by intrinsic values. As such, the existing social media usage framework and model do not consider the intrinsic motivations of senior entrepreneurs. Accordingly, in this study, a qualitative research approach through a single case study method was used. In-depth semi-structured interviews were also undertaken with ten (n=10) senior entrepreneurs to research the scenario of senior entrepreneurs' motivations and the data were thematically analyzed. Consequently, three themes emerged from the analysis, namely the motivations of senior entrepreneurs, the typology of senior entrepreneurs and the characteristics of business owned (combined as senior entrepreneurship activities), and the current ICT applications used. The themes were further categorized into attributes comprising four motivations (economic self-interest, social affirmation, active aging, and independence), four typologies of senior entrepreneurs (constrained entrepreneur, rational entrepreneur, reluctant entrepreneur, and lifestyle entrepreneur), characteristics of business owned (simple tasks, services type of business, and own physical store), and current ICT used (social media, e.g., Facebook, and social messaging application, e.g., WhatsApp). The model Facebook features in supporting senior entrepreneurship was developed based on the motivations of senior entrepreneurs integrated with Facebook features and the values of Facebook features identified through expert interviews. Verification through a paper prototype was also performed with four senior entrepreneurs who used Facebook for their businesses. Theoretically, this study has contributed to new knowledge through the development of the model of Facebook features in supporting senior entrepreneurship, and practically the model could be used as a guideline to identify Facebook features for senior entrepreneurs to take advantage of the existing social media facilities that their businesses require.